The Influence of Leader Character in Facing the Zillennial Generation in the Era of Industrial Revolution 4.0 - Hia, Vivian (Sekolah Tinggi Teologi Trinity Parapat, 2024)
Leaders who can adapt themselves to the conditions of the times are leaders who do not want to be outdated. In the era of industrial revolution 4.0, the influences both in terms of social life, education and so on. The purpose of this research is to thinking about problems of young people in an increasingly rapid era, namely presenting a leader who has transformative leadership characters. The method used in this research is the literature study method. Identifying all theories systematically, and analyzing containing information related to the topic. The results showed that leaders with integrity and who pay attention to the importance of character in leadership do not allow a situation to be in a tragic condition as experienced by the younger generation, a leader has a shared responsibility to not only guide and direct the people he leads but he must also be able to be an example.